Possible Applications of Creative Thinking within a Simplex Didactics Perspective - Iolanda Zollo; Maurizio Sibilio (Athens Institute for Education and Research, 2016)
The contemporary proteiform education system characterised by complexity and dynamism and brought about by the acknowledgement of the diversity in students' needs, requires teachers to constantly put into practice numerous problem-solving and decision-making strategies. The underpinning capability required to face challenging situations is a form of cognitive flexibility; i.e. the ability to find alternative solutions and strategies. This approach has been a subject to numerous studies and research, which provide worthy evidence on the role of creative thinking to apply detour strategies during the teaching-learning processes so as to respond to the inherent need to have a plurality of solutions to ensure a better control of the system at one's fingertips. The article presents the underpinning theory and the activities suggested for the organisation and delivery of the workshops sessions on simplex didactics aimed at in-service teachers and primary school pupils as part of a teacher-education course.